Comparison of Mesoamerican and Animistic Analog Systems of the Northwest Amazon - Otaegui, Alfonso Manuel (2008)
Starting from Descola's ideas (Par-déla Nature et Culturc: 2005), we make a comparison between an analogic system, the ~Vahuas from Mexico, and the systems from the Northwest Amazon that create problems in the classification because -altough described as animists- they resemble the analogists ones. Our main goal is tofind out what kind of systems could be generated by the different modes of identification, and if these configurations can explain these similarities. After underlying their logic components, we describe the systems that organise them. Although both of them -the Nahuas and the Northwest Amazon- have the ideas of circular causality, anorder organising /he relationships between the components o/ the world, the notion that individual actions dangerously affect the whole, these would be just surface effects,from systems whose components are too closely relaled. Even though there is a difference of intensity between both configurations, the harder version would be the Nahuas-one system, components below the level of individuality, idea of balance- and the softer one the Northwest Antmon-systein and sub-systems, conponents at the level of individuality. idea of stability-.We believe this difference of intensity is based on their difference in theirs modes of identification.